2021
DOI: 10.1002/cpz1.135
|View full text |Cite|
|
Sign up to set email alerts
|

SHIRPA as a Neurological Screening Battery in Mice

Abstract: sessment (SHIRPA) is a rapid battery of tests comprising 42 measurements of motor activity, coordination, postural control, muscle tone, autonomic functions, and emotional reactivity, as well as reflexes dependent on visual, auditory, and tactile modalities. Individual scores in SHIRPA are sensitive in detecting phenotypes of several experimental models of neural disease, especially cerebellar degeneration and Alzheimer disease, and combined subscores have been useful in estimating the impact of vascular anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…Autophagy has previously been shown to promote memory formation (Glatigny et al , 2019). To further characterize the effects of neuronal ATG5 deletion on mouse behavior, we employed the SmithKline, Harwell, Imperial College, Royal Hospital, Phenotype Assessment (SHIRPA)‐based test battery, which includes 22 measures of motor activity, postural control, emotional reactivity, and visual and auditory reflexes (Lalonde et al , 2021). We found that although mice lacking ATG5 in either excitatory or inhibitory neurons exhibited only minor neurological abnormalities (Appendix Fig S1H and I), both the Atg5 flox: CamKII α‐Cre and Atg5 flox :Slc32a1‐Cre KO lines responded with potentiated startle reflex to stimulus presentation compared to their control littermates (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy has previously been shown to promote memory formation (Glatigny et al , 2019). To further characterize the effects of neuronal ATG5 deletion on mouse behavior, we employed the SmithKline, Harwell, Imperial College, Royal Hospital, Phenotype Assessment (SHIRPA)‐based test battery, which includes 22 measures of motor activity, postural control, emotional reactivity, and visual and auditory reflexes (Lalonde et al , 2021). We found that although mice lacking ATG5 in either excitatory or inhibitory neurons exhibited only minor neurological abnormalities (Appendix Fig S1H and I), both the Atg5 flox: CamKII α‐Cre and Atg5 flox :Slc32a1‐Cre KO lines responded with potentiated startle reflex to stimulus presentation compared to their control littermates (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Gross phenotype assessment of motor and sensory function of aged mice was performed using elements of the primary screen of the SmithKline, Harwell, Imperial College, Royal Hospital, Phenotype Assessment (SHIRPA) test ( Rogers et al, 1997 ; Lalonde et al, 2021 ). This is a set of functional assessments that are designed to identify and systematically quantify abnormalities in murine muscle tone, lower motor neuron and spinocerebellar function, sensory and autonomic ability and motor coordination/capabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Like human neurological exams, rodent observational batteries often serve as a first-tier test to identify “an effect.” Examples include the Functional Observational Battery ( US EPA, 1994b ; Moser and Kallman, 2018 ; Gauvin, 2021 ) and the SmithKline, Harwell, Imperial College, Royal Hospital, Phenotype Assessment (SHIRPA) ( Rogers et al, 2001 ; Lalonde et al, 2021 ). Additional batteries have been developed for assessing vestibular dysfunction ( Maroto et al, 2021 ), various genetic manipulations ( Brown et al, 2000 ), and neonatal function ( Fox, 1965 ; Brown et al, 2000 ; Feather-Schussler and Ferguson, 2016 ; Soria-Ortiz et al, 2021 ).…”
Section: Behavioral Assessmentsmentioning
confidence: 99%